Oxygen evolution catalyst based on covalent organic framework structure and preparation method thereof

By introducing ferrocene ionic salts into the covalent organic framework structure COF-TpBpy, the FTMA@COF-TpBpy composite structure was formed, and the problems of high reaction rate and energy consumption of oxygen evolution catalysts were solved, and efficient and low-cost electrolytic water was achieved Hydrogen production catalytic properties.

CN119121286APending Publication Date: 2024-12-13ZHONGBEI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411295230.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-17
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing oxygen evolution catalysts have a slow reaction rate and a large overpotential during the electrolytic hydrogen production process, resulting in high energy consumption. The high iridium-based catalysts limit the development of scale, and the stability of non-iridium-based catalysts under harsh conditions. Sex and cost issues have not been effectively resolved.

Method used

Using the FTMA@COF-TpBpy composite frame structure based on the covalent organic framework structure, the ionic salt containing ferrocene catalytic sites is introduced into the COF-TpBpy material to form a nonvalent bond quaternized composite structure, thereby improving the structure of the catalyst Stability and oxygen evolution catalytic properties.

Benefits of technology

It realizes the increase in current density at a lower overpotential, reduces the Tafel slope, improves the electrochemical reaction efficiency and stability of the catalyst, reduces production costs, and has a wide range of application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121286A_ABST
    Figure CN119121286A_ABST
Patent Text Reader

Abstract

The invention discloses an oxygen evolution catalyst based on a covalent organic framework structure. Ionic salt (ferrocene methyl) trimethyl ammonium iodide containing a ferrocene catalytic site is introduced into a COF-TpBpy framework pore channel; according to the preparation method, ionic salt containing ferrocene catalytic sites is introduced into a COF-TpBpy material pore channel, the novel composite frame structure FTMA (COF-TpBpy with excellent structural stability and oxygen evolution electro-catalytic performance is prepared, and the composite frame structure FTMA (COF-TpBpy can be applied as an oxygen evolution catalyst in a water electrolysis hydrogen production reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials and relates to an oxygen evolution catalyst for producing hydrogen by electrolysis of water, and in particular to an oxygen evolution catalyst based on a covalent organic framework structure and a preparation method thereof. Background Art

[0002] Global energy use continues to increase, energy service costs continue to rise, and energy supply, climate and local air quality have all been negatively affected. Hydrogen energy, with its zero carbon content and high gravimetric energy density, is a promising clean energy carrier that meets the needs of global energy development.

[0003] Hydrogen production by water electrolysis can produce green hydrogen with no carbon emissions, which meets the needs of global energy development. It is a promising new energy power generation technology with good development prospects. At the technical level, water electrolysis hydrogen production technology uses low-cost non-precious metal catalysts and efficient and stable ion exchange membranes, which can significantly reduce the cost of key raw materials.

[0004] The process of hydrogen production by water electrolysis can be divided into two half-electrode reaction processes: hydrogen evolution at the cathode and oxygen evolution at the anode. Compared with the two-electron transfer at the positive electrode, the oxygen evolution reaction (OER) must undergo four electron transfer steps, and the energy accumulation between steps will lead to a large overpotential and a slow reaction rate, which is a bottleneck for various electrochemical applications. Under harsh industrial conditions, the development of efficient and stable oxygen evolution electrocatalytic materials is currently a major problem.

[0005] Iridium-based oxygen evolution catalysts are currently the most commonly used OER electrocatalytic materials, but the high price and low yield of iridium have greatly limited its large-scale development. Developing efficient and inexpensive non-iridium-based oxygen evolution catalysts to overcome the instability and high cost problems under harsh process conditions is one of the important topics in the research and development of highly stable and efficient oxygen evolution reaction electrocatalysts.

[0006] Covalent organic frameworks (COFs) are porous crystalline materials formed by covalently connecting light elements such as C, B, O and N. They are light in weight, low in density, high in specific surface area, regular and stable in structure, easy to be functionalized, and have good pore structure, chemical stability and thermodynamic stability. These characteristics enable them to form coordination with specific atoms in the organic framework by utilizing the constraint effect, provide a variable coordination platform for isolated metal atoms, and adjust the coordination environment of metal atoms; in addition, they can also achieve composite with other materials or design core-shell structures while maintaining the pore structure of the material. Such design strategies are helpful for the development of new materials with specific functions and properties, and show great potential for application in many fields such as gas storage and separation, catalysis, sensing, energy storage, and photoelectric conversion.

[0007] Although COFs materials have made a lot of progress in the field of electrocatalysis, there are still some problems to be solved. COFs materials without metal coordination lack active sites, resulting in low catalytic activity, which restricts their development in OER catalysts. Modifying COFs and improving their performance are of great significance for improving the oxygen evolution catalytic performance of OER catalysts.

[0008] Zhao Yuxiang et al. (Pyrimidine-Functionalized Covalent Organic Framework and itsCobalt Complex as an Efficient Electrocatalyst for Oxygen EvolutionReaction. ChemSusChem 2021, 14, 4556-4562.) A new type of COFs material modified with pyrimidine functional groups (COF-Pyr) was prepared by post-modification. The nitrogen atoms on the pyrimidine showed excellent coordination ability for metal ions, which is a new coordination strategy. Based on its large specific surface area and ordered crystal structure, the stable metal composite material Co@COF-Pyr obtained by loading cobalt ions showed excellent application performance in electrocatalytic oxygen evolution. However, the overpotential of its metal complex Co@COF-Pyr is large, and the current density reaches 10mA cm -2 A voltage of 450mV needs to be applied.

[0009] Yang, Q. et al. (In situ synthesis of covalent cobalt porphyrin framework / CNTs composites for efficient oxygen evolution reaction. Ionics 30, 4749-4759(2024).) A cobalt-porphyrin-based COFs material Co-COF / xCNT modified by CNT was prepared in situ. Due to the uniform distribution of active centers and the synergistic effect between Co-COF and CNT, the electrocatalyst showed excellent oxygen evolution reaction activity with a current density of 10 mA cm -2 The Tafel slope reaches 61mV dec -1 The reaction rate is fast, but its overpotential is 376mV, and the voltage required to be applied is slightly larger.

[0010] Although a lower Tafel slope indicates better kinetics and can achieve faster current density increase at a lower overpotential, higher energy may be required to drive the reaction to achieve the same current density in practical applications. Therefore, it is necessary to consider both the Tafel slope and overpotential parameters according to specific application requirements and goals. If the goal is to increase the reaction rate and reduce the amount of catalyst, the Tafel slope may be a more important indicator; if the goal is to reduce energy consumption and improve energy efficiency, the overpotential may be a more critical indicator.

[0011] Yang Zhaodi et al. (Novel Bifunctional Nitrogen Doped MoS2 / COF-C4N VerticalHeterostructures for Electrocatalytic HER and OER. Catalysts 2023, 13, 90.) A vertical heterostructure catalyst N-MoS2 / COF-C4N was prepared by an in-situ growth synthesis method. Due to its N-doped defect sites and vertical heterostructure, the C site of C4N is completely exposed, which has excellent OER activity and a current density of 10 mA cm -2 When a voltage of 349 mV is applied, the Tafel slope reaches 84 mV dec. -1 . Summary of the invention

[0012] The purpose of the present invention is to provide an oxygen evolution catalyst based on a covalent organic framework structure and a preparation method thereof, so as to construct a non-valent bond quaternized FTMA@COF-TpBpy composite framework structure with excellent structural stability and good oxygen evolution catalytic performance.

[0013] The oxygen evolution catalyst based on the covalent organic framework structure of the present invention uses COF-TpBpy as a framework, and introduces an ionic salt (ferrocenylmethyl) trimethylammonium iodide containing a ferrocenyl catalytic site into the COF-TpBpy pores to form a composite framework structure having a structure shown in the following structural formula (I):

[0014] The composite framework structure of the present invention is a reddish brown powder, insoluble in organic solvents, and the I in the (ferrocenylmethyl)trimethylammonium iodide ion salt is - Ions and N + The cations exist in the form of ionic bonds, and the ionic salts are confined within the pores of COF-TpBpy.

[0015] Furthermore, in the oxygen evolution catalyst based on the covalent organic framework structure of the present invention, the mass ratio of the COF-TpBpy framework to the ionic salt is 1:20-400.

[0016] Furthermore, the mass ratio of the COF-TpBpy framework to the ionic salt is more preferably 1:150-400.

[0017] On the other hand, the present invention also provides a method for preparing the oxygen evolution catalyst based on the covalent organic framework structure, specifically, the covalent organic framework material COF-TpBpy is preheated at 80-100° C. under a vacuum state, and then a methanol solution of the ionic salt (ferrocenylmethyl)trimethylammonium iodide is injected, and the ionic salt is impregnated under negative pressure under a vacuum state to allow the (ferrocenylmethyl)trimethylammonium iodide to be fully impregnated in the pores of COF-TpBpy, and after drying, a composite framework structure shown in structural formula (I) is formed.

[0018] Wherein, the preheating treatment is carried out in a continuous vacuum environment, and the preheating treatment time is preferably 24 to 30 hours.

[0019] Furthermore, the negative pressure impregnation of the ionic salt is carried out at 40-45° C., and the negative pressure impregnation time is preferably 30-48 hours.

[0020] It should be noted that the vacuum environment described in the present invention is not a complete vacuum environment, but a continuous negative pressure environment obtained by intermittent vacuuming by a vacuum pump.

[0021] In order to facilitate the negative pressure impregnation of the covalent organic framework material COF-TpBpy, the present invention also preferably performs ultrasonic crushing on the COF-TpBpy, specifically, the covalent organic framework material COF-TpBpy is dispersed in a dimethylformamide or N-methylpyrrolidone solvent system to form a suspension, and the suspension is crushed using an ultrasonic cell crusher, and the solvent is removed to obtain a refined COF-TpBpy material. The COF-TpBpy material after the refinement treatment is more conducive to the subsequent quaternization modification.

[0022] More specifically, the present invention preferably uses an ultrasonic cell disruptor with a power of 100 to 200 W to disrupt the suspension, and the preferred disruption time is 1.5 to 2 hours.

[0023] More preferably, the suspension may be cooled during the crushing process to maintain the temperature of the suspension at about 30°C.

[0024] Furthermore, the COF-TpBpy used as the framework in the present invention may be COF-TpBpy prepared by various reported preparation methods, and the present invention has no particular limitation thereto.

[0025] However, preferably, the COF-TpBpy described in the present invention can be an ion channel COF-TpBpy structure obtained by condensing trialdehyde pyrogallol and 5,5'-diamino-2,2'-bipyridine as raw materials in an N,N-dimethylaniline / 1,2-dichlorobenzene solvent system of acetic acid aqueous solution.

[0026] Specifically, the molar ratio of trialdehyde phloroglucinol to 5,5'-diamino-2,2'-bipyridine is preferably 1:1.5-2.

[0027] The present invention successfully prepared a new composite framework structure FTMA@COF-TpBpy with excellent structural stability and oxygen evolution electrocatalytic performance by introducing ionic salts containing ferrocene catalytic sites into the pores of the COF-TpBpy material. The FTMA@COF-TpBpy can be used as an oxygen evolution catalyst in the electrolysis of water to produce hydrogen.

[0028] The present invention peels off the multi-layer nanostructured COF-TpBpy into a single-layer nanostructure, and confines the (ferrocenemethyl)trimethylammonium iodide ion salt to the COF-TpBpy pores by negative pressure impregnation to construct a nano-impregnation "ferrocene" COFs structure to obtain FTMA@COF-TpBpy. Compared with the unmodified COF-TpBpy, the basic electrocatalytic performance of the catalyst is improved.

[0029] The preparation method of the non-valent bond quaternized FTMA@COF-TpBpy composite framework structure of the present invention is simple, the production cost is low, and it has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a comparison chart of infrared spectra (FTIR) of FTMA@COF-TpBpy and COF-TpBpy.

[0031] Figure 2 This is a comparison chart of X-ray photoelectron spectroscopy (XPS) between FTMA@COF-TpBpy and COF-TpBpy.

[0032] Figure 3 are transmission electron microscopy (TEM) images of FTMA@COF-TpBpy and COF-TpBpy.

[0033] Figure 4 It is the cyclic voltammetry (CV) curve of FTMA@COF-TpBpy and COF-TpBpy.

[0034] Figure 5 This is a comparison of the linear sweep voltammetry (LSV) curves of FTMA@COF-TpBpy and COF-TpBpy.

[0035] Figure 6 This is a comparison chart of the Tafel slopes of FTMA@COF-TpBpy and COF-TpBpy.

[0036] Figure 7 This is the electrochemical impedance spectroscopy (EIS) comparison diagram of FTMA@COF-TpBpy and COF-TpBpy.

[0037] Figure 8 This is a comparison chart of the double layer capacitance (Cdl) of FTMA@COF-TpBpy and COF-TpBpy. Implementation

[0038] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.

[0039] The production processes, experimental methods or detection methods involved in the embodiments and comparative examples of the present invention are all conventional methods in the prior art unless otherwise specified, and their names and / or abbreviations are all conventional names in the field and are very clear and unambiguous in the relevant application fields. Those skilled in the art can understand the conventional process steps based on the names and apply the corresponding equipment to implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0040] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art. Example

[0041] Example 1

[0042] Trialdehyde phloroglucinol (208 mg, 1 mmol) and 5,5'-diamino-2,2'-bipyridine (279 mg, 1.5 mmol) were dissolved in 20 ml of N,N-dimethylaniline / 1,2-dichlorobenzene mixed solution (1:1 v / v), placed in a 50 ml Teflon-lined autoclave, and ultrasonicated for 5 min to make it uniformly dispersed. Then, 2.7 ml of 6 mol L -1 The mixture was stirred with a magnetic stirrer for 2 h, sealed, and heated to 120 °C for 72 h.

[0043] The precipitate was collected by centrifugation, washed with anhydrous tetrahydrofuran (6×4 ml) and acetone (3×4 ml), respectively, and dried under vacuum at 80°C overnight to obtain orange-red COF-TpBpy with a yield of 65%.

[0044] Example 2

[0045] The COF-TpBpy prepared in Example 1 was ground into powder and dispersed in 50 ml of dimethylformamide solvent to form a suspension. The suspension was crushed for 1.5 h using an ultrasonic cell disruptor at a power of 200 W. During this period, the ultrasonic on / off time was set to 2 s and 3 s, respectively, and the suspension was circulated and cooled to keep the suspension temperature at about 30 °C.

[0046] The suspension was vacuum filtered, washed with methanol (15×3 ml), and dried overnight at 80° C. to obtain a finer orange-red COF-TpBpy powder.

[0047] Weigh 30 mg of the dried COF-TpBpy powder into a reaction bottle and evacuate for 2 min. Repeat the operation three times or more. Then, heat the reaction bottle to 80°C in an oil bath for 30 h, and evacuate every 5 h.

[0048] The quaternizing agent (ferrocenylmethyl)trimethylammonium iodide (0.578 g, 1.5 mmol) was weighed and dissolved in 2 ml of anhydrous methanol to prepare the quaternizing agent, which was slowly injected into the reaction bottle using a disposable syringe and reacted at 40° C. for 36 h.

[0049] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean Petri dish, and dried overnight at 80 °C in vacuum to obtain a deep red product FTMA@COF-TpBpy with a yield of 85%.

[0050] Example 3

[0051] The COF-TpBpy prepared in Example 1 was ground into powder and dispersed in 50 ml of dimethylformamide solvent to form a suspension. The suspension was crushed for 1.5 h using an ultrasonic cell disruptor at a power of 200 W. During this period, the ultrasonic on / off time was set to 2 s and 3 s, respectively, and the suspension was circulated and cooled to keep the suspension temperature at about 30 °C.

[0052] The suspension was vacuum filtered, washed with methanol (15×3 ml), and dried overnight at 80° C. to obtain a finer orange-red COF-TpBpy powder.

[0053] Weigh 30 mg of the dried COF-TpBpy powder into a reaction bottle and evacuate for 2 min. Repeat the operation three times or more. Then, heat the reaction bottle to 80°C in an oil bath for 24 h, and evacuate every 5 h.

[0054] The quaternizing agent (ferrocenylmethyl)trimethylammonium iodide (5.78 g, 15 mmol) was weighed and dissolved in 10 ml of anhydrous methanol to prepare the quaternizing agent, which was slowly injected into the reaction bottle using a disposable syringe and reacted at 40°C for 30 h.

[0055] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean Petri dish, and dried overnight at 80 °C in vacuum to obtain a deep red product FTMA@COF-TpBpy with a yield of 75%.

[0056] Example 4

[0057] The COF-TpBpy prepared in Example 1 was ground into powder and dispersed in 50 ml of dimethylformamide solvent to form a suspension. The suspension was crushed for 1.5 h using an ultrasonic cell disruptor at a power of 200 W. During this period, the ultrasonic on / off time was set to 2 s and 3 s, respectively, and the suspension was circulated and cooled to keep the suspension temperature at about 30 °C.

[0058] The suspension was vacuum filtered, washed with methanol (15×3 ml), and dried overnight at 80° C. to obtain a finer orange-red COF-TpBpy powder.

[0059] Weigh 30 mg of the dried COF-TpBpy powder into a reaction bottle and evacuate for 2 min. Repeat the operation three times or more. Then, heat the reaction bottle to 80°C in an oil bath for 30 h, and evacuate every 5 h.

[0060] The quaternary ammonium reagent (ferrocenylmethyl)trimethylammonium iodide (11.55 g, 30 mmol) was weighed and dissolved in 20 ml of anhydrous methanol to prepare the quaternary ammonium reagent, which was slowly injected into the reaction bottle using a disposable syringe and reacted at 40°C for 36 h.

[0061] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean Petri dish, and dried overnight at 80 °C in vacuum to obtain a deep red product FTMA@COF-TpBpy with a yield of 80%.

[0062] Example 5

[0063] The COF-TpBpy prepared in Example 1 was ground into powder and dispersed in 50 ml of N-methylpyrrolidone solvent to form a suspension. The suspension was crushed for 3 h using an ultrasonic cell disruptor at a power of 200 W. During this period, the ultrasonic on / off time was set to 2 s and 2 s, respectively, and the suspension was circulated and cooled to keep the suspension temperature at about 30 °C.

[0064] The suspension was vacuum filtered, washed with methanol (15×3 ml), and dried overnight at 80° C. to obtain a finer orange-red COF-TpBpy powder.

[0065] Weigh 30 mg of the dried COF-TpBpy powder into a reaction bottle and evacuate for 2 min. Repeat the operation three times or more. Then, heat the reaction bottle to 80°C in an oil bath for 24 h, and evacuate every 5 h.

[0066] The quaternary ammonium reagent (ferrocenylmethyl)trimethylammonium iodide (5.78 g, 15 mmol) was weighed and dissolved in 10 ml of anhydrous methanol to prepare the quaternary ammonium reagent, which was slowly injected into the reaction bottle using a disposable syringe and reacted at 40° C. for 48 h.

[0067] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean Petri dish, and dried overnight at 80 °C in vacuum to obtain a deep red product FTMA@COF-TpBpy with a yield of 78%.

[0068] Example 6

[0069] The COF-TpBpy prepared in Example 1 was ground into powder and dispersed in 50 ml of N-methylpyrrolidone solvent to form a suspension. The suspension was crushed for 3 h using an ultrasonic cell disruptor at a power of 200 W. During this period, the ultrasonic on / off time was set to 2 s and 2 s, respectively, and the suspension was circulated and cooled to keep the suspension temperature at about 30 °C.

[0070] The suspension was vacuum filtered, washed with methanol (15×3 ml), and dried overnight at 80° C. to obtain a finer orange-red COF-TpBpy powder.

[0071] Weigh 30 mg of the dried COF-TpBpy powder into a reaction bottle and evacuate for 2 min. Repeat the operation three times or more. Then, heat the reaction bottle to 100°C in an oil bath for 24 h, and evacuate every 5 h.

[0072] The quaternizing agent (ferrocenylmethyl)trimethylammonium iodide (5.78 g, 15 mmol) was weighed and dissolved in 10 ml of anhydrous methanol to prepare the quaternizing agent, which was slowly injected into the reaction bottle using a disposable syringe and reacted at 40°C for 30 h.

[0073] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean Petri dish, and dried overnight at 80 °C in vacuum to obtain a deep red product FTMA@COF-TpBpy with a yield of 78%.

[0074] Application Example 1

[0075] A nickel foam sheet with a size of 1×2 cm was treated with 3 mol / L hydrochloric acid solution, ultrapure water and anhydrous ethanol for 15 min each to remove surface oxides and organic molecules, and then dried in vacuum at 60°C for 6 h.

[0076] 2 mg of FTMA@COF-TpBpy prepared in Example 2 was weighed and dispersed in a mixed solution of 480 ml of anhydrous ethanol and 20 ml of 5 wt % Nafion, and then dispersed evenly by ultrasonication for 1 h.

[0077] Use a pipette to extract the dispersion and add it dropwise onto the nickel foam, extracting 3 ml each time, and adding it 20 times in total to ensure that the coverage area of ​​the nickel foam reaches 1 cm². Vacuum dry for 6 hours to prepare the FTMA@COF-TpBpy catalyst modified electrode.

[0078] Weigh the mass of nickel foam before and after the addition, and calculate the catalyst loading of the modified electrode to be 1.5 mg cm -2 .

[0079] Application Example 2

[0080] A nickel foam sheet with a size of 1×2 cm was treated with 3 mol / L hydrochloric acid solution, ultrapure water and anhydrous ethanol for 15 min each to remove surface oxides and organic molecules, and then dried in vacuum at 60°C for 6 h.

[0081] 2 mg of COF-TpBpy prepared in Example 2 was weighed and dispersed in a mixed solution of 480 ml of anhydrous ethanol and 20 ml of 5 wt % Nafion, and then dispersed evenly by ultrasonication for 1 h.

[0082] Use a pipette to extract the dispersion and add it dropwise onto the nickel foam, extracting 3 ml each time, and adding it 20 times in total to ensure that the coverage area of ​​the nickel foam reaches 1 cm². Vacuum dry for 6 hours to prepare the COF-TpBpy catalyst modified electrode.

[0083] Weigh the mass of nickel foam before and after the addition, and calculate the catalyst loading of the modified electrode to be 1.5 mg cm -2 .

[0084] The basic structure characterization of the FTMA@COF-TpBpy electrocatalyst and COF-TpBpy electrocatalyst loaded on nickel foam prepared in the above-mentioned application examples 1 and 2 is as follows: Figures 1 to 3 As shown, relevant electrochemical performance tests were also carried out, and the results are shown in Figures 4 to 8 .

[0085] Fourier transform infrared spectroscopy (FTIR) is an effective means of identifying and analyzing substances and can determine their structure. Figure 1Compared with COF-TpBpy, FTMA@COF-TpBpy has a -1 and 1440cm -1 The CN vibration peak of quaternary ammonium salt and 1450~1350cm -1 The methyl and methylene bending vibration peaks in the region prove that the quaternary ammonium salt has been successfully grafted onto COF-TpBpy.

[0086] and Figure 2 The I 3d3 and I 3d5 peaks of the electronic energy spectrum of FTMA@COF-TpBpy in the - The presence of Fe 2p peaks proves the successful introduction of ferrocene. These results also confirm that the nonvalent quaternization reaction of COF-TpBpy is successful.

[0087] Figure 3 The TEM analysis results show that the spherical clusters of the original COF-TpBpy in the left image are hollow, and the morphology of FTMA@COF-TpBpy is almost not damaged during the quaternization of the pores. However, due to the introduction of ionic salts, the TEM image of FTMA@COF-TpBpy becomes darker than that of COF-TpBpy, confirming the presence of ionic salts in the pores.

[0088] All electrochemical tests were performed on a standard three-electrode cell using an LViumSTAT electrochemical workstation. The catalyst-modified electrode was used as the working electrode (working electrode area 1 mA cm -2 ), platinum sheet as counter electrode, mercury oxide (Hg / HgO) electrode as reference electrode (reference electrode was calibrated before use), the electrochemical properties of the prepared catalysts such as LSV, EIS, CV, Tafel were tested in 1M KOH electrolyte, and the OER performance of the catalysts at room temperature was evaluated. All polarization curves were iR corrected and calculated according to the formula E RHE = E Hg / HgO +0.098+0.059× pH The recorded potential was converted into a reversible hydrogen potential.

[0089] Before the formal test, cyclic voltammetry was used in the potential range of -0.2 to -0.1 V vs RHE at 50 mV s -1 The catalyst working electrode was electrochemically activated for 100 cycles at a scan rate of 1.5 to reach a stable state.

[0090] Figure 4The results show that the FTMA@COF-TpBpy and COF-TpBpy have good conductivity at different scan rates (20 mV s) in the potential range of -0.2 to -0.1 V vs RHE. -1 , 40mV s -1 , 60mV s -1 , 80mV s -1 , 100mV s -1 ) under the CV curve. Take the absolute value of the current density difference at the intermediate potential ΔJ ,by ΔJ Plotted against the corresponding scan rate, half of the slope is the double layer capacitance Cdl. The larger the capacitance, the more active sites per unit area, which is more conducive to the oxygen evolution reaction.

[0091] Figure 5 The linear voltammetry (LSV) curve was used to evaluate the catalyst material at 5 mV s -1 OER performance at scan rates.

[0092] The overpotential (η) reflects the polarization degree and efficiency of the catalyst when current passes through it. The smaller the η value, the lower the additional voltage required to achieve the same current density, which can more effectively promote the reaction. Therefore, the smaller the η value, the better the OER performance.

[0093] The calculation formula of η value is η= E RHE -1.23, where 1.23V is the threshold for oxygen evolution at the lower electrode of the reversible hydrogen electrode, and the current density is 10mA cm −2 It is used as a benchmark threshold for evaluating electrocatalytic performance.

[0094] Compared with COF-TpBpy, the FTMA@COF-TpBpy catalyst modified electrode showed better OER catalytic activity. Specifically, in 1 M KOH alkaline solution, when the current density reached 10 mA cm -2 hour, Figure 5 The overpotential of FTMA@COF-TpBpy shown in the figure is 330 mV, which is significantly lower than the overpotential of COF-TpBpy of 400 mV, indicating that by introducing ferrocene-containing metal ion salt FTMA, the active sites on the catalyst surface can be increased, the efficiency of the electrochemical reaction can be improved, and thus the catalytic performance of OER can be effectively improved.

[0095] Figure 6 The Tafel slope in comes from Figure 5The LSV measurement shows the relationship between η and the logarithm of the current density. According to the Tafel equation, the Tafel slope of the FTMA@COF-TpBpy catalyst is 83.82 mVdec, which is inferred from the linear part of the Tafel plot. -1 , lower than COF-TpBpy (149.76mV dec -1 The lower the Tafel slope, the smaller the η required at the same current density, that is, the lower the polarization degree of the catalyst, and thus the higher the electrocatalytic activity.

[0096] Figure 7 The electrochemical impedance spectroscopy (EIS) test analysis was performed at 1.56 V vs RHE, with a frequency of 100,000 Hz to 0.01 Hz and an amplitude of 10 mV to evaluate the charge transfer ability of the catalyst material. The smaller the electrochemical impedance, the stronger the charge transfer ability. Figure 7 In the results, the charge transfer resistance of FTMA@COF-TpBpy is low, indicating that FTMA@COF-TpBpy effectively increases the active sites, reduces the charge transfer impedance, and enhances the charge transfer ability of the electrochemical system by introducing (ferrocenylmethyl)trimethylammonium iodide with better conductivity. Therefore, it has good conductivity and helps to improve the OER performance.

[0097] from Figure 8 according to Figure 4 From the Cdl graph obtained from the CV curve, it can be seen that FTMA@COF-TpBpy has the largest double-layer capacitance, indicating a higher electrochemical specific surface area and the ability to expose more catalytic active sites.

[0098] The above results show that porous structure electrodes usually have a larger specific surface area. Appropriate metal doping can provide more contact points and channels for the penetration of electrolytes and provide more available active surface area, making it easier for ions in the electrolyte to reach the electrode surface, increasing the number of active sites involved in the reaction and improving the catalytic activity of the catalyst.

[0099] The following Table 1 also provides a comparison of electrochemical performance indicators of COF-related catalysts reported in Example 2 and some literature. According to the data in Table 1, it can be seen that the comprehensive performance of FTMA@COF-TpBpy is better than that of several published coordinated COFs.

[0100]

[0101] [1] Yang, Q., Fan, Y., Zhou, H. et al. In situ synthesis of covalentcobalt porphyrin framework / CNTs composites for efficient oxygen evolution reaction. Ionics 30, 4749-4759 (2024).

[0102] [2] Y. Zhao, Y. Yang, T. Xia, H. Tian, ​​Y. Li, Z. Sui, N. Yuan, X.Tian, ​​Q. Chen. Pyrimidine-Functionalized Covalent Organic Framework and itsCobalt Complex as an Efficient Electrocatalyst for Oxygen EvolutionReaction. ChemSusChem 2021, 14, 4556.

[0103] [3] Zhang, N.; Yang, Z.; Liu, W.; Zhang, F.; Yan, H. NovelBifunctional Nitrogen Doped MoS2 / COF-C4N Vertical Heterostructures for Electrocatalytic HER and OER. Catalysts 2023, 13, 90.

[0104] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Those skilled in the art may make various changes, modifications, substitutions and variations to these embodiments without departing from the principles and purpose of the present invention, which shall all be included in the protection scope of the present invention.

Claims

1. An oxygen evolution catalyst based on a covalent organic framework structure, which uses COF-TpBpy as a framework, and introduces an ionic salt (ferrocenylmethyl) trimethylammonium iodide containing a ferrocenyl catalytic site into the COF-TpBpy pores to form a composite framework structure having a structure shown in the following structural formula (I): 。 2. According to the oxygen evolution catalyst based on the covalent organic framework structure according to claim 1, the mass ratio of the COF-TpBpy framework to the ionic salt in the oxygen evolution catalyst is 1:20-400.

3. The oxygen evolution catalyst based on the covalent organic framework structure according to claim 2, Its characteristics are The mass ratio of COF-TpBpy framework to ionic salt is 1:150-400.

4. The preparation method of the oxygen evolution catalyst based on the covalent organic framework structure according to claim 1 is to preheat the covalent organic framework material COF-TpBpy at 80-100° C. under vacuum, then inject a methanol solution of the ionic salt (ferrocenylmethyl)trimethylammonium iodide, and perform negative pressure impregnation of the ionic salt under vacuum to fully impregnate the (ferrocenylmethyl)trimethylammonium iodide in the pores of COF-TpBpy, and form a composite framework structure shown in structural formula (I) after drying.

5. The preparation method according to claim 4, Its characteristics are Preheat treatment in a continuous vacuum environment for 24 to 30 hours.

6. The preparation method according to claim 4, Its characteristics are Immerse under negative pressure at 40-45°C for 30-48 hours.

7. The preparation method according to claim 4 is characterized in that before the preheat treatment, COF-TpBpy is dispersed in a dimethylformamide or N-methylpyrrolidone solvent system to form a suspension, and an ultrasonic cell disruptor is used to perform ultrasonic disruption treatment to remove the solvent to obtain a refined COF-TpBpy material.

8. The preparation method according to claim 7, Its characteristics are The suspension was disrupted using an ultrasonic cell disruptor with a power of 100 to 200 W.

9. The preparation method according to claim 8, Its characteristics are Crushing 1.5~2h。 10. Use of the oxygen evolution catalyst based on the covalent organic framework structure according to claim 1 as a catalyst for producing hydrogen by electrolysis of water.

Citation Information

Cited By

  • Green and efficient method for electrochemically synthesizing olefin by transferring hydrogen atoms in water through electrocatalysis

    CN120138650A